Proficiency level in English teachers of the Seventh-day Adventist elementary schools in the North Mexican Union Conference - Galina Pogorelova (Anuario de Investigación UM, 2020)
Today, using foreign languages effectively has become essential. English is, without a doubt, the most expanded language of communication with more than a billion speakers and has come to be considered the lingua franca that everyone must learn to have higher chances of professional success. There is plenty of evidence from teaching experience and the literature to suggest that English language proficiency is an essential aspect of EFL teaching and teacher expertise. This study aims to evaluate the English proficiency level in teachers of the Seventhday Adventist elementary schools in the North Mexican Union Conference, applying the Michigan Test. the studied population were the elementary school teachers who teach English in the Adventist schools of the North Mexican Union Conference. The total of participants were 24 teachers. 54,2% of participants are women and 45,8% are men. Out of 24 participants just 3 teachers have a degree in English teaching, but almost all of them received a certification for teaching English; 2 participants are native English speakers. 33,3% of participants had studied in Adventist universities. The examination was used to collect data for this study. The examination was designed from the Michigan Practice Tests for the sections of grammar, vocabulary, reading and listening, and from TOEFL and a Ted Talk video for the speaking section. The findings obtained by the examination in the LimeSurvey that wasapplied to the 24 English teachers showed that they have strengths in the Listening and Speaking skills, but they have weaknesses in the Reading skills. In general, most of the teachers got a good level in the English proficiency that respond to the Teacher Profile requirements.